Adoption of blended e-learning among Malaysian academicians / Nor Aini Abd Rahman - Abd Rahman, Nor Aini (2011)
This research reports on adoption of blended e-learning among Malaysian academicians in Malaysia. Many higher learning institutions in Malaysia have implemented blended e-learning because of its effectiveness as a learning approach. However, studies have shown that academicians are apprehensive about teaching in blended e-learning. The theoretical framework for this study is based on Mezirow's Transformational Learning Theory, Technology Acceptance Model and Technology Readiness Index. In the Transformational Learning Theory, the frame of reference for an individual will influence his/her action. Technology Acceptance Model focuses on the acceptance of technology through perceived usefulness and perceived ease of use. Six independent variables namely educational technology preference, learning goals, personal incentives, perceived ease of use, perceived usefulness and technology readiness were tested for their relationship with the adoption of blended e-learning. Four dimensions from Technology Readiness Index: optimism, innovativeness, insecurity and discomfort also were tested for their relationship with adoption of blended e-learning. The study employed the quantitative method approach. Data were gathered through surveys among academicians in two public universities in Malaysia of which are among the pioneers in blended e-learning adoption. Sixty five academicians who adopted blended e-learning responded. Data were analyzed using statistical packages software, SPSS. The reliability analysis was conducted in order to ensure the internal validity and consistency of the items used for each variables. The six independent variables were tested for their correlation with adoption of blended e-learning using Spearman's correlation test. All variables were found to have significant correlation with adoption of blended e-learning. Findings from this study provide insights on the factors that influenced the adoption of blended e-learning. It is found that perceived usefulness is factor that most influenced the adoption of blended e-learning. Its practical contribution includes knowledge which can be incorporated into the e-learning training modules to address the problem of low adoption of blended e-learning.